Affrication of Occlusive Consonants and Palatalization - Balšaitytė, Danutė (Respectus Philologicus, 2005)
The article focuses on one of the possible ways to express the distinctive feature „hardness-softness“ in Lithuanian and Russian consonants (the increase in the duration of their explosive phase ), i.e.affrication of consonants.The choice of the material and the methodology of the research is determined (I) by the theoretical and practical significance of the problem of how distinctive features of phonemes are phonetically expressed in the related languages and (II) by the fact that the influence of palatalisation on the formation of the stops in Lithuanian has not been studied at large.The carried out contrastive analysis of the spectral properties of the soft and hard stops in Lithuanian and Russian has helped to determine some similarities in the actualisation of the occlusive consonants in both languages and to describe the peculiarities in the acoustic expression of palatalisation in the spectrum of the Lithuanian stops. Contrary to the Russian language, in which palatalisation leads to the change in the way of stop formation, viz. to the appearance of the affricative phase, in Lithuanian, the regular palatalisation can be found only in the labial voiced consonant [b’]. The explosive phase of the palatalised occlusive consonants before various vowels may exceed the duration of the glottal phase of the corresponding hard stop, coincide with it, or maybe shorter. In other words, the stops in Lithanian do not differ in ‘hardness-softness’. The Russian stops [t’] and [d’] are characterised by the most regular and strong affrication. In contrast, for the Lithuanian [t’], (d’], the affrication is not regular ( only in individual positions) and weak (compared with the back-tongued and labial consonants). Positioned before the back tongue vowels, the Russian consonants are affricated less than before other vowels, while the duration of explosion in the Lithuanian consonants rapidly increases before [‘u:].